Islam Kejawen in Action: Melestarikan Kearifan Budaya Lokal sebagai Upaya Alternatif Menangkal Radikalisme Agama dan Pengaruh Modernisasi - Sultoni, Agus (Momentum : Jurnal Sosial dan Keagamaan, 2019)
Abstract: Kejawen Islam is a product of an Islamic process with a cultural assimilation model that gives rise to the tradition of syncretism. Da'wah by giving Islamology and its history is not effective enough in the process of Islamization in various parts of the region, including even in Western society. A formal, dogmatic radical approach can even trigger problems. Kejawen Islam has a prerequisite for it, through a cultural approach that will provide more coolness and minimize horizontal conflicts as exemplified by the previous senior ulema, Walisanga. This paper wants to revive, preserve and grow Javanese culture in shaping the attitudes and behavior of the young generation in finding identity as a nation that has a great culture - especially as an effort to counteract religious radicalism and the influence of modernization. Kejawen teachings which are considered by some to be ancient, are very relevant to be learned in modern life, which are full of changes and very rapid and radical advances which have frustrated many people here and there.